Effect of an Antioxidant Based on Red Beetroot Extract on the Abiotic Stability of Polylactide and Polycaprolactone - Drohsler, Petra; Cisar, Jaroslav; Sopik, Tomas; Sedlarik, Vladimir; Pummerova, Martina (Molecules (Basel, Switzerland), 2021)
This study investigated the effect of natural antioxidants inherent to beetroot (Beta vulgaris var. Vulgaris) on the ageing of environmentally friendly plastics. Certain properties were examined in this context, comprising thermal, mechanical, and morphological properties. A visual evaluation of relevant changes in the given polymers (polylactide and polycaprolactone) was conducted during an ageing test in a UV chamber (45 °C, 70% humidity) for 720 h. The films were prepared by a casting process, in which samples with the extract of beetroot were additionally incorporated in a common filler (bentonite), this serving as a carrier for the extract. The results showed the effect of the incorporated antioxidant, which was added to stabilize the biodegradable films. Its efficiency during the ageing test in the polymers tended to exceed or be comparable to that of the reference sample.
Keywords: fyziologický stres; abiotic stability; Plant Extracts; Polyesters; biodegradable polymer; Plastics; plastické hmoty; Bentonite; Antioxidants; degradation; Vegetables; rostlinné extrakty; zelenina; antioxidant; Stress, Physiological; polylactide; antioxidancia; polyestery; kořeny rostlin; polycaprolactone; beetroot; Beta vulgaris; Plant Roots; bentonit